Prinsip Dan Kode Etik Dalam Bisnis - Amalia, Lutfi; Rahmaningtiyas, Niken Faizah; Sarpini, Sarpini (FEB Universitas Maritim Semarang, 2024)
Abstract. The research investigates the principles and ethical codes in business, highlighting their critical role in today's competitive environment. As businesses face increasing pressure to balance financial success with ethical conduct, the study aims to define these concepts, explore their scope, and identify key ethical principles while examining their implementation in Islamic banking. Employing a qualitative methodology, the research analyzes literature and case studies to understand the frameworks guiding ethical business practices. Findings reveal that principles such as honesty, social responsibility, and fairness are essential for fostering trust among stakeholders and enhancing corporate reputation. The implications stress the necessity for businesses to integrate these ethical codes into their operations actively, as doing so not only builds a positive public image but also contributes to long-term sustainability. Furthermore, the study identifies challenges in applying these standards, emphasizing that overcoming such obstacles is vital for creating a fair business ecosystem that benefits all parties involved.